Coverage evaluation of Mass Drug Administration (MDA) for lymphatic filariasis in a district of Bundelkhand Region of Uttar Pradesh - Barman, Santosh Kumar; Kumar, Navin; Barman, Seema; Maroof, Mohd; Chouhan, Ravi Raj Singh; Yadav, Mukesh (Indian Journal of Community Health, 2022)
Introduction: Lymphatic filariasis results in severe disability that leading to severe social and economic burden at each level from individual to family, and community. This study was carried out to assess the coverage and compliance of MDA. Methods: From 300 households (1837 individuals) in both rural & urban area were covered in coverage evaluation survey by systematic selection of subunits using probability proportionate to size (PPS). Each household was visited by WHO designated team and data were collected using predesigned questionnaire. Data was compiled on MS-excel spreadsheet, frequency and percentage were calculated. Results: The overall effective coverage for all drugs was low (19.1%). The coverage was low, compliance was higher in urban as compared to rural area. Females had better coverage and compliance than males. The primary reasons for drug not offered was nobody came to offer drug, drug not swallowed was not sick, drug swallowed was useful information from drug administrator (DA). Only one female reported adverse effect. Conclusion: Increase in coverage along with decrease in coverage-compliance gap is needed to achieve filariasis elimination that warrants intense IEC activities using different platforms, development of better drug delivery strategies and strengthening monitoring system.